KEEFEKTIFAN PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING PENDEKATAN KONTEKSTUAL DENGAN PETA KONSEP PADA SISWA KELAS VIII SMP NEGERI 2 SUNGGUMINASA - Hartati Ramli (Universitas Sulawesi Barat, 2019)
The research was experiment research which aimed to discover the effectiveness of the implementation of discovery learning model of contextual approach with concept map in Mathematics learning in Cubes and Blocks Material in class VIII at SMPN 2 Sungguminasa. The populations of the research were all of the students in class VIII at SMPN 2 Sungguminasa and the sample was one class, namely class VIII-2 as the experiment class which was chosen by using cluster random sampling technique. The data of the research consisted of the students’ activities in learning, students’ responses, and students’ learning results. The data of the students’ activities were analyzed descriptively and the data of students’ responses and students’ learning results were analyzed descriptively and inferentially. The result of the research revealed that: (1) the implementation of discovery learning model of contextual approach with implemented well, (2) the implementation of discovery learning model of contextual approach with concept map was effective based on the aspects: (a) the students’ learning result with the average score of activity implementation 3.89 (very active category); (b) the students’ responses with the average score 3.81 (positive category); (c) the students’ learning results with the average score of post test 87.55 Minimum Completeness Criteria, the average score of gain 0.87, and the pecentage of classical completeness which had been fulfilled was 91,67% 80%. The result of hypothesis test in significant level 0.05 with t-test show that the discovery learning model of contextual approach with concept map is effective to be implemented in mathematics learning in Cubes and Blocks material to students’ of class VIII at SMPN 2 Sungguminasa.